Farmer's risk perception, and seroprevalence and associated risk factors of Toxoplasma gondii in small ruminants and backyard chickens in selected districts of West Gojjam Zone, Northwest Ethiopia - Morar-Leather, Darshana (University of Pretoria, 2025)
Mini Dissertation (MSc (Veterinary Science))--University of Pretoria, 2024.